Preserve and Reuse or Destroy and Rebuild? Losing the UK’s Twentieth-Century Building Legacy and Sustainable Ways to Save and Repurpose It - Celia Clark (ARCHive-SR)
Useful, reusable buildings that embody communities’ history, identity and aspirations are currently being lost, and their embodied carbon wasted by demolition. Key twentieth-century buildings that could be reused are being destroyed by a combination of factors that need reform if their potential for adaptive reuse as contributions to sustainability and progress towards carbon neutrality is to be acknowledged. It is hoped that this paper, based on UK experience, has a wider relevance since the reuse of buildings is a worldwide contribution to achieving net carbon zero. It is time to take demolition off the table, but currently, there are UK legislative hurdles unfavourable to this change of direction. Historic buildings are lost as a result of the narrowness of Historic England’s preservation criteria for Listing. The widening of Permitted Development Rights facilitates demolition without consultation or planning permission. There is weakness in the underfunded local authority planning system, while tax inequity charges 20% VAT on restoration but not on new building. We need to change our throw-away culture and remove these obstacles to reusing our historic building stock - to the benefit of both the climate and the sustainable future of our communities.